Myeloma cell growth suppression by osteoblast-derived extracellular vesicles: the creation of a non-permissive niche for myeloma cells by bone-forming osteoblasts - SooHa Kim; Jumpei Teramachi; Masahiro Hiasa; Ryota Amachi; Ariunzaya Bat-Erdene; Asuka Oda; Hirofumi Tenshin; Mariko Tanaka; Motosumi Nakagawa; Aiko Seki; Yoshihiko Sawa; Ken-ichi Matsuoka; et al. (Haematologica)
Not available.